Growing up with a single mother and life satisfaction in adulthood: A test of mediating and moderating factors. - David Richter; Sakari Lemola (PLoS ONE, 2017)
Single parenthood is increasingly common in Western societies but only little is known about its long-term effects. We therefore studied life satisfaction among 641 individuals (ages 18-66 years) who spent their entire childhood with a single mother, 1539 individuals who spent part of their childhood with both parents but then experienced parental separation, and 21,943 individuals who grew up with both parents. Individuals who grew up with a single mother for their entire childhood and to a lesser degree also individuals who experienced parental separation showed a small but persistent decrease in life satisfaction into old age controlling childhood socio-economic status. This decrease was partly mediated by worse adulthood living conditions related to socio-economic and educational success, physical health, social integration, and romantic relationship outcomes. No moderation by age, gender, and societal system where the childhood was spent (i.e. western oriented FRG or socialist GDR) was found.